The Clinical Epidemiology of Spontaneous ICH in a Sub-Sahara African Country in the CT Scan Era: A Neurosurgical In-Hospital Cross-Sectional Survey - Adeleye, Amos Olufemi; Osazuwa, Uyiosa A.; Ogbole, Godwin I. (Frontiers in Neurology, 2015)
Background There is paucity of data-driven scientific reports from sub-Saharan Africa on the burden of spontaneous intracerebral hemorrhage (sICH). We have maintained a prospective consecutive in-hospital database of cases of sICH referred for neurosurgical intervention over a 5-year period. Methods This is a cross-sectional descriptive study of the clinical epidemiology and brain computed tomography (CT) characterization of sICH from the database in this region in the current era. Results There were 63 subjects, 38 (60.3%) males, aged 28–85 years, mean 55.7 (SD, 12.7), the modal age distribution being the sixth decade. Uncontrolled hypertension was the main predisposition in the study: present, premorbid, in 79%, but uncontrolled in 88% of these known cases, and exhibited malignant derangements of blood pressure in more than half. The clinical ictus to in-hospital presentation was delayed, median 72 h; was in severe clinical state in 70%, 57% was comatose; and was complicated with fever in 57% and respiratory morbidity in 55.6%. The main clinical symptomatology was hemiparesis, headache, vomiting, and aphasia. The sICH was supratentorial on brain CT in 90.5%, ganglionic in 50.8%, and thalamic in 58.3% of the latter. The bleed had CT evidence of mass effect and intraventricular extension (IVH) in more than half. Twenty-three patients (36.5%) underwent operative interventions. Conclusion In this patient population, sICH is mainly ganglionic and thalamic in location with significant rate of associated IVH. In-hospital clinical presentation is delayed, and in a critical state, the bleeding is uncontrolled hypertension related in >95%.